2021
DOI: 10.1111/cns.13694
|View full text |Cite
|
Sign up to set email alerts
|

Spinal microglial β‐endorphin signaling mediates IL‐10 and exenatide‐induced inhibition of synaptic plasticity in neuropathic pain

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 105 publications
(231 reference statements)
1
14
0
Order By: Relevance
“…It is known that proinflammatory cytokines such as TNF‐α, IL‐1β, and IL‐6 are released in the spinal dorsal horn in response to a variety of pain stimuli. 3 , 39 , 40 , 41 , 42 This was demonstrated in the present study in PSNL mice, which showed increases in all three cytokines. Interestingly, PSNL‐induced increases in the cytokines, in particular TNF‐α and IL‐1β, were reversed by inhibition of PDE4 with either rolipram or roflumilast.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It is known that proinflammatory cytokines such as TNF‐α, IL‐1β, and IL‐6 are released in the spinal dorsal horn in response to a variety of pain stimuli. 3 , 39 , 40 , 41 , 42 This was demonstrated in the present study in PSNL mice, which showed increases in all three cytokines. Interestingly, PSNL‐induced increases in the cytokines, in particular TNF‐α and IL‐1β, were reversed by inhibition of PDE4 with either rolipram or roflumilast.…”
Section: Discussionsupporting
confidence: 81%
“…It is known that proinflammatory cytokines such as TNF‐α, IL‐1β, and IL‐6 are released in the spinal dorsal horn in response to a variety of pain stimuli 3,39–42 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, microglia can modify synaptic activity by releasing molecules such as IL-33 [ 173 ] and IL-1 β [ 55 ]. Alternatively, microglial release of BDNF [ 169 ] or IL-10 [ 178 180 ] can also modulate spine formation. Moreover, microglia can modulate spine density by releasing TNF- α [ 181 , 182 ] or IL-10 [ 178 ].…”
Section: Microglial Regulation Of Synapsis Structure and Functionmentioning
confidence: 99%
“…Recent studies showed that the activation of the GLP1/GLP1R axis improved recognition memory impairment, neuroinflammation, and neurological pain via regulating the AMP-activated protein kinase/nuclear factor kappa B (AMPK/NF-κB) pathway [ 102 , 103 ]. Further, the GLP1R agonist decreases pain hypersensitivity through decreasing pro-inflammatory factors and increasing microglia anti-inflammatory factors, such as interleukin 10 (IL-10), cluster of differentiation 206 (CD206), interleukin 4 (IL-4), and arginase 1 (Arg1) [ 102 , 104 , 105 , 106 , 107 , 108 ]. New research claimed that the gene regulation in response to GLP1R activation is an effective strategy in new treatments for neuropathic pain, by confirming that the GLP1R pathway is involved in pain hypersensitivity mediated by microglia activation [ 109 ].…”
Section: Enteroendocrine Cells In Visceral Pain and Neuropathic Painmentioning
confidence: 99%